Spice up your online class with Gather Town / Muhammad Aiman Abdul Halim - Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2021)
By now, most educators including myself have successfully adapted with various virtual meeting platforms such as Google Meet, Zoom and Webex. From our experience using all these different platforms, we can easily notice some similarities and differences in features which could either be appealing or not for classroom use. Some platforms are more user-friendly and easier to use, while others might be a bit complicated, but offer more tools and security features. There are so many options out there and it is our responsibility as educators to choose which platform is best for our students’ needs. Gather Town is one of the platforms that I had recently discovered, which seems to have great potential in establishing interesting and interactive online classes. Do not feel left out if you have never heard about it because Gather Town is a relatively new virtual meeting platform that was just launched on 3rd April 2021.